Perceptions of people with intellectual and developmental disabilities about COVID‐19 in Spain: a cross‐sectional study. Issue 5 (8th February 2021) - Amor, A. M.; Navas, P.; Verdugo, M. Á.; Crespo, M.
Abstract: Background: As the world battles COVID‐19, there is a need to study the perceptions of people with intellectual and developmental disabilities (IDD) about the effects of the pandemic and associated lockdown on their lives. This work explores the perceptions of Spaniards with IDD during the lockdown with respect to four topics: access to information, emotional experiences, effects on living conditions and access to support . Methods: The topics were explored using a subset of 16 closed‐ended questions from an online survey. In total, 582 participants with IDD completed the survey. The frequencies and percentages of responses to the questions were calculated, and chi‐square tests performed to explore the relationship between participants' sociodemographic characteristics and responses. Given that people differed in the way in which they completed the survey, the relationship between participants' responses and completion method was also analysed. Results: Participants reported that the pandemic and subsequent lockdown have had a deleterious effect on their emotional well‐being (around 60.0% of participants) and occupations (48.0% of students and 72.7% of workers). Although access to information and support was reportedly good overall, being under the age of 21 years and studying were associated with perceptions reflecting poorer access to information ( V = .20 and V = .13, respectively) and well‐being support ( V = .15 and V = .13, respectively). Being supported by a third party to complete the survey was consistently related to perceptions of worse outcomes. Conclusions: The study yielded data on the perceptions of people with IDD regarding the effects that COVID‐19 and the subsequent lockdown have had on their lives. Suggestions on how to overcome the difficulties reported and future lines of research are discussed.